List-Chromatic Number and Chromatically Unique of the Graph Kr2 + Ok (Selecciones Matemáticas, 2019)
In this paper, we determine list-chromatic number and characterize chromatically unique of the graph G = Kr2 +Ok. We shall prove that ch(G) = r + 1 if 1
Keywords: Chromatic number; list-chromatic number; chromatic polinomial; chromatically unique graph; complete r-partite graph